Effectiveness of Gestalt Therapy on Happiness of Elderly People - Heiman Saadati; Jalal Younesi; Mahshid Foroghan; Leila Lashani (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: The aim of this study was to examine the effectiveness of Gestalt therapy on the happiness of elderly people. Methods & Materials: This is an experimental study with a pre-test- post-test design and control group. Sample of the study selected from elderly members of Shad Senior Social Club. 50 older members were evaluated according to inclusion/ exclusion criteria and by Abbreviated Mental Test Score. 28 participants selected and divided into 2 equal groups randomly. Oxford Happiness Scale was administered to both. Gestalt therapy sessions for the intervention group were administered in 90 minutes weekly meetings for 8 successive weeks. The post-test data collected after the last session. Data analyzed by using t-test for independent groups. Results: T-test results showed that the mean difference between the two groups were significant (P<0.01) and Gestalt therapy increased the happiness of intervention group significantly. Happiness scores of intervention group in all sub-scales were also significantly higher in post-test compared to control group (P<0.001). Conclusion: The results showed that Gestalt therapy can be helpful in enhancing positive emotions and happiness in older people. Implementation of Gestalt therapy sessions in nursing homes, and retirement centers are recommended.